Zafrira Lidovsky Cohen. Loosen the Fetters of thy Tongue, Woman: The Poetry and Poetics of Yona Wallach. Cincinnati: Hebrew Union College Press, 2003. x, 264 pp. - Ostriker, Alicia 1937- (2004)
Think of the intensity and notoriety of Sylvia Plath in the English-speaking world, and multiply it several times: that is Yona Wallach for the Hebrew-speaking world today. The most passionate and flamboyant figure in postwar literary Israel, Wallach was born on a small farming village in 1944, lived there most of her life until her death of breast cancer in 1985, and after her death has become a cultural legend. In life Wallach experimented with sex, drugs, and madness (she checked herself into a mental hospital in 1964 and remained for three months, deliberately exploring what the subconscious yielded), was a compelling live performer of her poems, and was typically surrounded by worshipful younger writers. In her art she was yet more experimental. Her poetry combines mysticism, sexuality, an ecstatic love of nature and a correspondingly powerful mistrust of society and its conventions, a fascination with language and the breakdown of language, an insistence on the validity of freedom and will. Steeped in biblical allusions, mythology, fairy tales, and kabbalistic imagery, she often twists and turns her sources with playful or violent irony. Her lexicon swerves through extremes of exaltation and crudeness. Her verse sometimes is traditionally rhymed, more often unpredictably and jazzily ragged, her imagery is often surreal, her narratives elliptic, her syntax fractured—yet thrillingly readable.
Keywords: Rezension